2012
DOI: 10.1088/0967-3334/33/8/1363
|View full text |Cite
|
Sign up to set email alerts
|

Automated criterion-based analysis for Cole parameters assessment from cerebral neonatal electrical bioimpedance spectroscopy measurements

Abstract: Hypothermia has been proven as an effective rescue therapy for infants with moderate or severe neonatal hypoxic ischemic encephalopathy. Hypoxia-ischemia alters the electrical impedance characteristics of the brain in neonates; therefore, spectroscopic analysis of the cerebral bioimpedance of the neonate may be useful for the detection of candidate neonates eligible for hypothermia treatment. Currently, in addition to the lack of reference bioimpedance data obtained from healthy neonates, there is no standardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Optimization of depth sensitivity in EIS measurement using the dual-energy SGF excitation pulses also has the potential to help develop proposed future point-of-care clinical applications, such as ICH and stroke detection [7], [8], [10], [46], [47] as well as noninvasive assessment of brain tumors [48], arteriovenous malformations, and radiation injury [49], cervical intraepithelial neoplasia [50], perinatal hypoxia [51] and asphyxia [52], [53], thyroid nodules classification [54], and functional electrical stimulation efficacy [55], epilepsy [56], [57], and general brain function [58]. …”
Section: Discussionmentioning
confidence: 99%
“…Optimization of depth sensitivity in EIS measurement using the dual-energy SGF excitation pulses also has the potential to help develop proposed future point-of-care clinical applications, such as ICH and stroke detection [7], [8], [10], [46], [47] as well as noninvasive assessment of brain tumors [48], arteriovenous malformations, and radiation injury [49], cervical intraepithelial neoplasia [50], perinatal hypoxia [51] and asphyxia [52], [53], thyroid nodules classification [54], and functional electrical stimulation efficacy [55], epilepsy [56], [57], and general brain function [58]. …”
Section: Discussionmentioning
confidence: 99%
“…3 Currently, in addition to the limited data available on BIA in newborns, mainly preterm ones, there is no consensus on the methodological standardization of this exam for this population. 4 For instance, it has been suggested that being attached to a monitoring wire precludes the performance of the BIA. However, the continuous monitoring of several physiological parameters is required to maintain the safety of newborns in intensive care.…”
Section: Introductionmentioning
confidence: 99%
“…The spectra of MLS and chirp pulse both have a continuous plateau envelope where most of the energy is concentrated. But in most BIS applications, only a discrete set of frequencies is required to fit the impedance data to a model like Cole equation [20], and BIS devices usually need to perform measurements at several to tens of isolated frequencies (usually with large frequency intervals) over a wide range of frequencies (often from 5 kHz to 1 MHz) [21]. Consequently, wideband excitation signal whose energy is distributed mainly in finite frequency points with large frequency spacing is ideal for BIS measurements.…”
Section: Introductionmentioning
confidence: 99%